Medlemsundersökning SÖDRA Skog - Torstensson, Anna (SLU/School for Forest Management, 2009)
This report is prepared in cooperation with Södra, Norra Halland SBO. The survey gives the members an opportunity to influence the services and also gives the staff at Södra a hint of the member’s demands. Södra is the largest co-operative forest company in Sweden with over 50 000 members and is divided into 31 areas. Norra Halland SBO is one of them. A questionnaire was sent to the members and 516 (or 53 %) of them answered. Of the respondents 68 % were between 60 and 69 years of age. All the questions are not reported here considering to the comprehensive material. Men are generally more interested than women in participating in Södra`s different members´ activities such as `forest days´ and `forest evenings´. The lack of interest in taking part in different activities has been a problem for the forest companies during a long time, also in Södra. To solve this problem, activities must be arranged in the right place, at the right time and with the right subject. The members are fairly satisfied with the different services that are offered, except when it comes to silviculture, such as planting and pre-commercial thinning where 22 % of the respondents declare that they are partly unsatisfied with the services. For services related to thinning more than 32 % declare that they are very satisfied. Even if the members are satisfied, service management should be developed and members treated in a more individualized way.